Impact of agricultural support on environmental and climate objectives - Ankai Xu (World Trade Organization (WTO), 2023)
This note synthesises the available literature examining the impact of agricultural support on greenhouse gas (GHG) emissions as well as its impact on water, biodiversity, and land. In keeping with the Secretariat's impartiality, the note reports the findings as they appear in the literature. The primary source of analysis is the work conducted by Ash and Cox (2022), supplemented by additional insights from recent literature on this subject.
Keywords: 330; agriculture; environment; climate change